The Influence of Age Diversity on Organizational Identification - Waligóra, Łucja (Wpływ różnorodności wiekowej na identyfikację organizacyjną, 2025)
Aim: The aim of this study was to determine the role of employee age heterogeneity in building a sense of belonging to the organization and to recognize the impact of human resource management activities and an inclusive climate on this relationship. Methodology: This study synthesizes the existing literature and presents empirical research conducted in 30 organizations in Poland. Quantitative data were collected from HR managers and rank-and-file employees, and diverse statistical analyses were conducted to verify the hypotheses. Results: While age diversity alone was not directly related to organizational identification, HR activities supportive of all age groups and a welcoming organizational environment significantly mediated this relationship. Implications and recommendations: The findings highlight the importance of applying human resource policies inclusive of different age groups and cultivating a welcoming organizational environment to enhance organizational identification. Future research should further explore the mechanisms and contexts in which age diversity impacts organizational identification, considering industry and cultural differences. Originality/value: This research contributes to the understanding of the dynamics connecting age group variation with identification with the workplace, offering valuable insights for HR management and organizational development in promoting an inclusive and supportive work environment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 152-163